KETERAMPILAN SAINS MELLUI PEMBELAJARAN SAINS DAN TEKNOLOGI ANAK USIA 4-6 TAHUN DI TK IT Al-KAHFI - Dike Paradiba; Nabilla Khusnul Irawan; Tsamrotul Fuadah; Windi Dwi Andika; Yuni Dwi Suryani (Early Childhood: Jurnal Pendidikan, 2025)
Early childhood is at a golden developmental period, where curiosity and the ability to learn through experience are very high. Therefore, it is important to develop science skills through experiment-based learning and environmental exploration. This study aims to look at the development of children's science skills, assess the extent of children's understanding of science and technology concepts, and identify the benefits of experimental activities. The research method used was qualitative, with participatory observation techniques, interviews, and documentation of 29 children at IT Al-Kahfi Kindergarten. Data were analyzed by data reduction, data presentation, and conclusion drawing. The results show that experimental activities such as rainbow bridges, color rain, and rocket launches are able to increase children's interest in learning, curiosity, understanding of scientific concepts, and critical thinking skills. In addition, experiments also train motor skills and cooperation between children. The implementation of science and technology learning at an early age is proven to be effective in supporting children's overall cognitive and social development.